Degradation of Components of the Lpt Transenvelope Machinery Reveals LPS-Dependent Lpt Complex Stability in Escherichia coli - Martorana, Alessandra M.; Moura, Elisabete C. C. M.; Sperandeo, Paola; Di Vincenzo, Flavia; Liang, Xiaofei; Toone, Eric; Zhou, Pei; Polissi, Alessandra (Frontiers in Molecular Biosciences, 2021)
Lipopolysaccharide (LPS) is a peculiar component of the outer membrane (OM) of many Gram-negative bacteria that renders these bacteria highly impermeable to many toxic molecules, including antibiotics. LPS is assembled at the OM by a dedicated intermembrane transport system, the Lpt (LPS transport) machinery, composed of seven essential proteins located in the inner membrane (IM) (LptB2CFG), periplasm (LptA), and OM (LptDE). Defects in LPS transport compromise LPS insertion and assembly at the OM and result in an overall modification of the cell envelope and its permeability barrier properties. LptA is a key component of the Lpt machine. It connects the IM and OM sub-complexes by interacting with the IM protein LptC and the OM protein LptD thus enabling the LPS transport across the periplasm. Defects in Lpt system assembly result in LptA degradation whose stability can be considered as a marker of an improperly assembled Lpt system. Indeed, LptA recruitment by its IM and OM docking sites requires correct maturation of the LptB2CFG and LptDE sub-complexes, respectively. These quality control checkpoints are crucial to avoid LPS mistargeting. To further dissect the requirements for the complete Lpt transenvelope bridge assembly, we explored the importance of LPS presence by blocking its synthesis using an inhibitor compound. Here we found that the interruption of LPS synthesis results in the degradation of both LptA and LptD, suggesting that in the absence of the LPS substrate the stability of the Lpt complex is compromised. Under these conditions, DegP, a major chaperone-protease in Escherichia coli, is responsible for LptD but not LptA degradation. Importantly, LptD and LptA stability is not affected by stressors disturbing the integrity of LPS or peptidoglycan layers, further supporting the notion that the LPS substrate is fundamental to keep the Lpt transenvelope complex assembled and that LptA and LptD play a major role in the stability of the Lpt system.